Is it Possible to Wake Sleeping People and Non-Human Animals by Staring at Them? - Sheldrake, Rupert; Smart, Pam (Journal of Scientific Exploration, 2024)
Some people say that they can wake sleeping people or sleeping non-human animals by staring at them. We investigated the natural history of these claims by examining more than 240 accounts submitted to us over a 30-year period by informants in the UK, US, Germany and several other countries. Most of these reports, 145 cases, concerned waking sleeping dogs and cats by staring at them; some described waking people up by looking at them, and some accounts were from people who had been woken by looks from animals or by other people. When animals were woken by people’s stares, 26% of them were said to have responded directionally by looking straight at the person who was watching them. Some people said that they themselves responded directionally to the stares of animals or other people as they woke, but the proportion of directional human responses was significantly lower (11%) than animal responses. Several informants said that animals were harder to wake by staring at them when they were dreaming. In most cases, possible explanations in terms of subtle sounds or chance coincidence seem unlikely. The ability to be woken by stares may involve a form of perception as yet unrecognized by science, for which we suggest the name scopegersis, from the Greek roots scop = “look at” and egersis = “awakening”. This putative ability seems closely related to the ability of people and many species of animals to feel the looks of unseen others when they are awake, known as the sense of being stared at or scopaesthesia. In both cases these responses may depend on the activity of the superior colliculus, a mid-brain region concerned with orientation towards environmental stimuli. These sensitivities may have evolved in the context of predator prey-relationships. We suggest experimental tests for investigating scopegersis in more detail.